Penerapan Model Pembelajaran Creative Problem Solving untuk Meningkatkan Keaktifan dan Kemampuan Memecahkan Masalah Pembelajaran Manajemen Strategi - Bayu Surindra; Elis Irmayanti (Proceedings of The ICECRS, 2019)
In general, an education has a meaning as a life process in developing itself to be able to carry out life in the hope of increasing and developing human resources as a whole. Education in the scope of higher education is expected to direct student to be able to think critically, actively, creatively, and be able to solve problems, so that the interaction between lecturers and students is expected to be good and conductive. Effective learning is two-way learning that is between lecturers and students giving real contributions to each other in the learning process. This is line with the development of education today especially in college wheres the learning is centered on student participant,hopefully more active in learning. So many models of learning to increase of student creativity in learning process one of the alternative learning models is the creative problem solving learning model. This study has a goal that is to improve student activity and problem solving skills in strategy management learning. And the method used in this study is to use two cycles of classromm action research method at level III student of the economic education study program at the Nusantara PGRI University Kediri. From the research that has been done, it can be conclusion that in general the application of activity problem solving can improve student activeness and problem solving skills in strategy management learning.